Vehicle Dynamics Model as Road Pavement Load Generator - Lozia, Z. (Engineering Transactions, 2000)
This paper presents the models of vehicle that are treated as road pavement load generators for different motion cases. The key role of a tire model is discussed. The most complicated 14 degrees of freedom truck model is based on the structure of a biaxial vehicle with dependently suspended front and rear wheels. The road pavement is treated as rigid but uneven. The road irregularities have a determined 3D form and may also be the realisation of stationary Gaussian random process describing the real road according to ISO recommendations. The paper shows specific model application for generation of forces between tires and uneven road. The vehicle response (for given motion cases, e.g. straight constant velocity motion) may be presented as time histories of footprint forces as well as force’s PSD. The simulation results may be treated as input data for the road pavement stress and wear analysis.